Systematic review on mental health in the context of COVID-19 - N. León, Carmen (2022)
The current situation made it possible to visualize the counterproductive impact on attending to people's mental health. On the one hand, workers, students, and health personnel requiredattention for the treatment of certain psychological discomforts. Even nosocomios were affected in their mental health prevention and promotion programs. Therefore, this research aims toanalyze the contributions on mental health during the pandemic. The methodology used was the systematic review, in addition to the PRISMA flowchart was applied for the selection ofindexed articles. The main contributions have shown that mental health underwent changes in the treatment and follow-up of patients. In addition, the groups affected have been workers, studentsin regular and higher education, and health workers. These groups were directly affected by isolation, resulting in an imbalance in their mental health. Among the main consequenceswas an increase in anxiety, depression and stress. Finally, the strategies used suggest the use of physical activities, changing habits and establishing schedules for the control of activities.